The use of bounce in professional wheelchair tennis - Sánchez-Pay, A.; Torres-Luque, G.; Sanz-Rivas, D.; Courel-Ibanez, J. (International Journal of Sports Science & Coaching, 2020)
The purpose of this study was to determine the influence of the use of bounce on performance in wheelchair tennis. Data pertaining to all the hits on the ball (n = 4021) were recorded from 16 men`s singles professional matches. Performance parameters regarding to players` skill level (high- and low-ranked) the game situation (players and the serve-return situation), technical-tactical aspects (hitting side), and outcome (stroke and point outcome) were included in multivariate regression and decision tree models. The results determined that the skill level ( 2(1) = 7.164, p > 0.01) and stroke outcome ( 2(2) = 14.099, p > 0.01) were the main predictors of the number of bounces, with high-ranked players using more bounces than the low-ranked. Stroke outcome was the main distinguishing factor of the use of bounce ( 2(4) = 51.424, p < 0.01, V = 0.08), with a greater use of zero bounces in winners and errors, one bounce in rallies, and two bounces in winners. These findings should be taken into consideration by coaches to design specific training systems according to the requirements from wheelchair tennis.